Analysis of the main components precursors of occupational accidents in the construction industry in Spain (2003–2022) - De-las-Heras-Rosas, Carlos Javier; Suárez-Cebador, Manuel; Salguero-Caparrós, Francisco Miguel; Rubio-Romero, Juan Carlos (Elsevier, 2025)
The construction industry is one of the most influential sectors in the economy of many societies; in the European Union, it contributes 5.5 % of GDP. However, it is also one of the most dangerous sectors worldwide due to its high occupational accident rate. The aim of this research is to identify the elements that are considered precursors of occupational accidents in the construction sector. To this end, 40,582 cases of serious and fatal accidents that occurred in Spain between 2003 and 2022 were examined. Although the contributing factors and accident typologies in the construction industry exhibit considerable variability, the Principal Component Analysis conducted allowed for the identification of five groups of variables that capture the key characteristics of occupational accidents, accounting for 64.2 % of the total variance. Among the most significant findings are the worker’s experience, the presence of moving objects, electrical risks, falls from different heights, the execution of activities far from the usual place of work, and the size of the company. The results of this research will enable a more focused effort in developing effective strategies to reduce occupational accidents in this sector. The identification of precursor agents of occupational accidents in construction, based on the variables examined, will help determine which specific areas require priority attention.
Keywords: Higiene y seguridad laboral; Industria de la construcción; Precursors; Safety Management; Construction industry; Serious and fatal accidents; Principal Component Analysis (PCA)